2008
DOI: 10.1002/bjs.6175
|View full text |Cite
|
Sign up to set email alerts
|

Prospective study of bone scintigraphy as a staging investigation for oesophageal carcinoma

Abstract: Bone is frequently the first site of identifiable distant metastatic spread, and bone scintigraphy is recommended to exclude metastatic disease before radical treatment of advanced oesophageal carcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(14 citation statements)
references
References 25 publications
0
12
0
2
Order By: Relevance
“…Au Japon, dans une série de 44 patients présentant un cancer de l’œsophage, 2 cas de métastases costales ont été rapportés; tandis que dans la série de Jennings, 11 cas de métastases costales ont été répertoriés sur 719 cancers œsophagiens colligés [3, 4]. …”
Section: Discussionunclassified
“…Au Japon, dans une série de 44 patients présentant un cancer de l’œsophage, 2 cas de métastases costales ont été rapportés; tandis que dans la série de Jennings, 11 cas de métastases costales ont été répertoriés sur 719 cancers œsophagiens colligés [3, 4]. …”
Section: Discussionunclassified
“…a radiografia mostra frequentemente lesões ósseas osteolíticas 7 . o padrão atual de prática para a detecção de doenças metastáticas é cintilografia óssea convencional de todo o corpo usando o tecnécio -99 m metileno difosfonato (tc-99m MdP) 11 . a tomografia por emissão de pósitrons (Pet), com 18-F-fluorodeoxyglucose (Pet-FdG), mostra em estudo, na detecção de metástases ósseas, 92 % de sensibilidade, especificidade de 94% e acurácia de 93%, em comparação com 77%, 84% e 82%, respectivamente, para cintilografia óssea 5 .…”
Section: Discussionunclassified
“…For patients receiving esophagectomy, the bone metastasis events were recorded until death or the last follow-up. Bone recurrence was defined as bone metastasis detected as the first site of recurrence after esophagectomy or detected within 1 month of first site of recurrence after esophagectomy [ 7 , 13 ]. For patients who did not receive esophagectomy, the bone metastasis events were recorded within 6 months of initial bone scan.…”
Section: Methodsmentioning
confidence: 99%
“…Quint et al [ 12 ] suggested that routine preoperative bone scan identifies metastases only in the presence of widespread metastatic or unresectable locoregional disease within the abdomen and thorax. Nevertheless, Jennings et al [ 13 ] reported that skeletal system is frequently the first site of identifiable distant metastatic spread, and bone scan is recommended to exclude metastatic diseases before radical treatment of esophageal cancer. Most importantly, the majority of esophageal cancers in previous studies evaluating the role of bone scan [ 4 , 12 , 13 ] are esophageal adenocarcinoma, not esophageal squamous cell carcinoma.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation